Journalism in the Digital Age : Comparing Traditional Print News and Online News Sources in the U.S. - Larson, Eric A.; Johnson, Sara; Christenson, Eric; Rosenberry, Sam; Van Natta, Jessi (My University, 2011)
The purpose of this study was to find which news source (i.e. newspapers or online news) college students preferred and the reasons why.
Color poster with text and graphs.
Keywords: College students--Attitudes--United States; Online journalism; Newspapers; Posters; News audiences; Consumers' preferences